Enhanced optoelectronic quality of perovskite films with excess CH3NH3I for high-efficiency solar cells in ambient air. (26th April 2017) - Zhang, Yunhai; Lv, Huiru; Cui, Can; Xu, Lingbo; Wang, Peng; Wang, Hao; Yu, Xuegong; Xie, Jiangsheng; Huang, Jiabin; Tang, Zeguo; Yang, Deren
Abstract: Solution-processed polycrystalline perovskite films contribute critically to the high photovoltaic performance of perovskite-based solar cells (PSCs). The inevitable electronic trap states at grain boundaries and intrinsic defects such as metallic lead (Pb 0 ) and halide vacancies in perovskite films cause serious carrier recombination loss. Furthermore, the film can easily decompose into PbI2 in a moist atmosphere. Here, we introduce a simple strategy, through a small increase in methylammonium iodide (CH3 NH3 I, MAI), molar proportion (5%), for perovskite fabrication in ambient air with ∼50% relative humidity. Analysis of the morphology and crystallography demonstrates that excess MAI significantly promotes grain growth without decomposition. X-ray photoemission spectroscopy shows that no metallic Pb 0 exists in the perovskite film and the I/Pb ratio is improved. A time-resolved photoluminescence measurement indicates efficient suppression of non-radiative recombination in the perovskite layer. As a result, the device yields improved power conversion efficiency from 14.06% to 18.26% with reduced hysteresis and higher stability under AM1.5G illumination (100 mW cm −2 ). This work strongly provides a feasible and low-cost way to develop highly efficient PSCs in ambient air.